Implementation of Production Scheduling To Find Out Delays in Clothing Products to Consumers Using the Plan, Do, Check, Action (PDCA) and Shortest Processing Time (SPT) Methods: Case Study: Al Ghani Convection - Muzammil, Abdulloh; Nuruddin, Moh.; Hidayat, Hidayat (Universitas Syiah Kuala, 2023)
The research was conducted at Al Ghani Convection, a company engaged in the convection sector. The research focused on the application of production planning and scheduling methods using the Plan, Do, Check, Action (PDCA) framework and the Shortest Processing Time (SPT) method. The study begins by introducing Al Ghani Convection, a company engaged in the convection of raw materials into finished products, especially manual t-shirts, and press prints. The production approach follows a make-to-order model, resulting in delays due to scheduling problems and raw material availability. To overcome these challenges, this study uses the PDCA framework and the SPT method. The PDCA approach involves planning, executing, inspecting, and acting phases. This focus is on setting a well-structured production schedule based on customer demand and optimizing the use of available resources. The SPT method prioritizes production based on the fastest time so as to increase efficiency in production scheduling. Through data analysis, the study concluded that the PDCA method, together with the SPT technique, effectively improves production planning, scheduling, and material procurement. The SPT approach helps reduce the average production delay to around 0.5 days. Recommendations include procuring starting materials, routine inventory checks, and providing customers with estimated production times.